Development of a Biosimilar of Agalsidase Beta for the Treatment of Fabry Disease: Preclinical Evaluation - André B. P. van Kuilenburg; Carla E. M. Hollak; Ana Travella; Melisa Jacobs; Lucas D. Gentilini; René Leen; Karen M. M. Ghauharali-van der Vlugt; Femke S. Beers Stet; Susan M. I. Goorden; Sanne van der Veen; Marcelo Criscuolo; Mariana Papouchado (Adis, Springer Healthcare, 2023)
Abstract Background and Objective Fabry disease (FD) is a rare lysosomal storage disorder caused by a deficiency of the enzyme α-galactosidase A (aGal A). Since 2001, two different enzyme replacement therapies have been authorized, with agalsidase beta being used in most parts of the Western world. Currently, biosimilars of several expensive enzyme therapies are under development to improve their accessibility for patients. We present the preclinical results of the development of a biosimilar to agalsidase beta. Methods Produced in a Chinese hamster ovary (CHO)-cell system, the biosimilar aGal A Biosidus (AGABIO), was compared with agalsidase beta with respect to amino acid sequence, glycosylation, specific α-galactosidase activity, stability in plasma, and effects on cultured human Fabry fibroblasts and Fabry mice. Results AGABIO had the same amino acid composition and similar glycosylation, enzymatic activity, and stability as compared with agalsidase beta. After uptake in fibroblasts, α-galactosidase A activity increased in a dose-dependent manner, with maximum uptake observed after 24 h, which remained stable until at least 48 h. Both enzymes were localized to lysosomes. Reduction of accumulated globotriaosylceramide (Gb3) and lysoGb3 in cultured Fabry fibroblasts by AGABIO and agalsidase beta showed comparable dose-response curves. In Fabry knockout mice, after a single injection, both enzymes were rapidly cleared from the plasma and showed equal reductions in tissue and plasma sphingolipids. Repeated dose studies in rats did not raise any safety concerns. Anti-drug antibodies from patients with FD treated with agalsidase beta showed equal neutralization activity toward AGABIO. Conclusion These findings support the biosimilarity of AGABIO in comparison with agalsidase beta. The clinical study phase is currently under development.